THE DEVELOPMENT OF STUDENTS’ ENGLISH WORKSHEET BASED ON PHONETIC TRANSCRIPTION AT THE TENTH GRADE OF MA MA’ARIF ROUDLOTUT THOLIBIN METRO - Anggun Tika Safita; Mai zuniati (Journal of English Development)
Education is a conscious and planned effort to create a good learning atmosphere and learning process so that students actively develop their potential. But so far the teacher only uses textbooks only to provide material and questions without training students' pronunciation, because in the textbooks the pronunciation is small and even the teacher doesn't pay attention to students in pronunciation. So that development is needed for the learning process. This study aims to develop a Worksheet based on Phonetic transcription class X MA MA'arif Roudlotut Tholibin 28 Purwosari north Metro. This research is a research and development study. The steps in this research are: Potential and Problems, Data Collection, Product Design, Product Revision, Product Validation, Product Trial, Revision After Trial. The results of this study in the form of a Phonetic transcription class X-based Science Worksheet can be used in the learning process at MA Ma'arif Roudlotut Tholibin 28 Purwosari north Metro, based on responses and validator ratings of the developed teaching materials, obtained results categorized as good. This shows that teaching materials developed based on phonetic transcription in class X can be used as teaching materials for MA MA'arif Roudlotut Tholibin 28 Purwosari north Metro students.